Joint optimization of LCMV beamforming and acoustic echo cancellation for automatic speech recognition - Herbordt, Wolfgang; Nakamura, S.; Kellermann, Walter (2005 IEEE International Conference on Acoustics, Speech, and Signal Processing, ICASSP '05, 2005)
For full-duplex hands-free acoustic human/machine interfaces, often a combination of acoustic echo cancellation and speech enhancement in order to suppress acoustic echoes, local interference, and noise is required. In order to optimally exploit positive synergies between acoustic echo cancellation and speech enhancement, we presented in an earlier work a combined least-squares (LS) optimization criterion for the integration of acoustic echo cancellation and adaptive linearly-constrained minimum variance (LCMV) beamforming [1]. In this contribution, we illustrate the efficiency of the proposed solution in situations with high levels of background noise and with time-varying echo paths and frequent double-talk by speech recognition experiments. ©2005 IEE